Strategi Komunikasi Kepemimpinan Kepala Sekolah Perempuan SMK Islam PB Soedirman 1 Jakarta - Aninda Meirawati (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
Female leadership in technical education encounters dual challenges: entrenched masculine norms and persistent gender stereotypes. This study aims to analyze the communication strategies employed by the female principal of SMK Islam PB Soedirman 1 Jakarta in constructing personal branding as a means of overcoming gender-based barriers. Using a qualitative approach with a case study method, data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that the principal leverages consistent public communication, active social media engagement, and value-driven role modeling rooted in Islamic principles as core elements of her personal branding. These strategies not only enhance her credibility and self-confidence but also shift public perceptions regarding women's leadership capabilities in technical education institutions. The study concludes that authentic, value-based personal branding plays a crucial role in fostering socially accepted, transformative female leadership in Islamic vocational education settings.